A Multiphase Routing Scheme in Irregular Mesh-Based NoCs - Duan, Xinming; Li, Yuanyuan (2011 Fourth International Symposium on Parallel Architectures, Algorithms and Programming, 2011)
At present, typical application-specific NoC systems often integrate a number of heterogeneous components which have varied functions, sizes and communication requirements. Instead of regular topology networks, constructing irregular mesh topology network on chip (NoCs) becomes an attractive approach to building future NoC systems with irregular structure. Deadlock-free routing control algorithm is a promising problem for irregular mesh topology. The available routing algorithms from regular mesh are not suitable for irregular mesh network. So in this paper, we introduce a hybrid scheme multiphase routing algorithm for irregular mesh integrating oversized rectangle modules. The basic idea of the scheme is borrowed from the area of fault tolerant networks, where a network topology is rendered irregular due to fault regions. The proposed scheme only employs 2 virtual channels per physical channel with fast routing decisions. In the case that the proposed two-phase routing scheme does not keep connection between some pairs of nodes, certain healthy nodes are deactivated to guarantee its deadlock-freeness. A greedy method is presented to ensure that only the minimum nodes are deactivated.